Effect of different cropping conditions, depth of burial, age of seeds, and allelopathic effect of different crops on the germi-nation behavior of little seed canary grass (Phalaris minor Retz.) seeds - Prabhakar , Sivapuram Venkata Rama Krishna; Yaduraju , N. T.; Dadlani , Malavika; Gopal , M. (Plant Breeding and Seed Science, 2012)
Pot culture experiments were conducted to find out the effect of different cropping conditions, depth of burial and age of seeds on the survival of little seed canary grass (Phalaris minor Retz.) seeds. The results indicated that the soil temperature modifications through the flooding or filed capacity moisture status of the soil influenced the germination and viability of the buried weed seeds rather than the crops per se. It was observed that the seeds lost their viability because of the anaerobic conditions and high temperatures and through increased membrane permeability of the seeds. The P. minor Retz. seeds were found to be sensitive to anaerobic conditions. The longevity of seeds buried in rice-wheat system and Flooding-wheat system was found low when compared to those buried under soybean-wheat and field capacity-wheat conditions. The in situ effect of rainy season (kharif) crops was found to confine to influencing the initial germination (vigor) of the little seed canary grass with cowpea, groundnut, soybean and sunflower inhibiting the initial germination of little seed canary grass. This inhibition was absent at the end of germination counts taken after twenty days after keeping for germination. The residual effect of cowpea, rice, soybean and sunflower was observed. The application of pearl millet and rice residues has considerably reduced the little seed canary grass germination, plant height, seedling fresh weight and leaf area at thirty days after sowing.